PENGARUH KUALITAS PRODUK DAN ATRIBUT PRODUK TERHADAP LOYALITAS PELANGGAN PADA SUSU CAIR UHT FRISIAN FLAG (Studi Kasus Pada Pembeli UHT Frisian Flag Usia 20-35 Tahun di Semarang) - Irawati Iriani; Agus Hermani (Universitas Diponegoro, 2016)
to sell and still can carry out its operations. Product quality and productattributes is one of the important factors that could affect the level of customer loyalty inFrisian Flag UHT dairy beverage products. With the presentation of a good qualityproduct and quality and a good and interesting attributes of the product, it will furtherenhance the level of consumer loyalty Frisian Flag UHT milk in making a purchase on anongoing basis.This type of research is explanatory. With a total sample of 100 respondentswere taken in three districts in Semarang. Collecting data using a questionnaire with Likertscale measurement. Data analysis methods used are validity and reliability, the correlationcoefficient (R), a simple linear regression, multiple linear regression, coefficient ofdetermination (R2), F test and t test. The results of this study concluded that the quality ofthe products and product attributes have a strong influence positive and significant impacton customer loyalty, either partially or simultaneously. Product quality and productattributes together have a strong influence on customer loyalty proved by the correlationcoefficient (R) of 0.900.